Penyelesaian Perkara Wanprestasi pada Perjanjian Hutang Piutang Tanpa Sita Jaminan (Studi Kasus Putusan Nomor 146/Pdt.G/2021/PN Bpp) - Rayna Candra Kirana Putri; Ery Arifudin (Fakultas Hukum Universitas Islam Indonesia, 2023)
This thesis aims to analyze and find out the settlement of default cases in debt and credit agreements without collateral confiscation (Case Study of Decision Number 146/Pdt.G/2021/PN Bpp). This research raises two problem statements, specifically why is the settlement of default cases in debt and credit agreements carried out without security confiscation (Case Study of Decision Number 146/Pdt.G/2021/PN Bpp)? and what are the consequences of case settlement in debt and credit agreements without security confiscation (Case Study of Decision Number 146/Pdt.G/2021/PN Bpp)? This research uses normative research using a conceptual approach, statutory approach, and case approach. Based on the results of the research, the conclusion can be reached the settlement of default cases in debt and credit agreements in Decision Number 146/Pdt.G/2021/PN Bpp was carried out without a collateral confiscation because the collateral confiscation of the land requested by the plaintiff included a PLTU installation and included a State-Owned Enterprise that could not be used as a collateral confiscation, and referred to the Technical Guidelines for Administration and Technical General Civil Courts where in number 11 the judge did not conduct a collateral confiscation of shares, because if he violated it, it would be a violation of the Code of Ethics. As a result of the refusal of collateral confiscation in the verdict, there is no realization of the law certainty, and the principle of good faith in an agreement is not implemented. And there are some recommendations, among others: there is a separate rule that discusses the practice of implementing collateral confiscation of stocks in order to create legal certainty, and it is hoped that the Panel of Judges when making decisions in a case will pay attention to the realization of the form of legal certainty, and also the principle of good faith.